Geology of the Utah Frontier Observatory for Research in Geothermal Energy (FORGE) Enhanced Geothermal System (EGS) Site - Clay Jones; Stuart Simmons; Joseph Moore (Geothermics, 2024)

Unlocking the hidden value of industrial by-products: Optimisation of bioleaching to extract metals from basic oxygen steelmaking dust and goethite - Ipek Tezyapar Kara; Nuannat Simmons; Stuart T. Wagland; Frederic Coulon (Chemosphere, 2023)

Establishing the Foundation for the Global Observing System for Marine Life - Erin V. Satterthwaite; Nicholas J. Bax; Patricia Miloslavich; Lavenia Ratnarajah; Gabrielle Canonico; Daniel Dunn; Samantha E. Simmons; Roxanne J. Carini; Karen Evans; Valerie Allain; Ward Appeltans; Sonia Batten; et al. (Frontiers in Marine Science, 2021)
Maintaining healthy, productive ecosystems in the face of pervasive and accelerating human impacts including climate change requires globally coordinated and sustained observations of marine biodiversity. Global coordination is predicated on an understanding of the scope and capacity of existing monitoring programs, and the extent to which they use standardized, interoperable practices for data management. Global coordination also requires identification of gaps in spatial and ecosystem coverage, and how these gaps correspond to management priorities and information needs. We undertook such an assessment by conducting an audit and gap analysis from global databases and structured surveys of experts. Of 371 survey respondents, 203 active, long-term (>5 years) observing programs systematically sampled marine life. These programs spanned about 7% of the ocean surface area, mostly concentrated in coastal regions of the United States, Canada, Europe, and Australia. Seagrasses, mangroves, hard corals, and macroalgae were sampled in 6% of the entire global coastal zone. Two-thirds of all observing programs offered accessible data, but methods and conditions for access were highly variable. Our assessment indicates that the global observing system is largely uncoordinated which results in a failure to deliver critical information required for informed decision-making such as, status and trends, for the conservation and sustainability of marine ecosystems and provision of ecosystem services. Based on our study, we suggest four key steps that can increase the sustainability, connectivity and spatial coverage of biological Essential Ocean Variables in the global ocean: (1) sustaining existing observing programs and encouraging coordination among these; (2) continuing to strive for data strategies that follow FAIR principles (findable, accessible, interoperable, and reusable); (3) utilizing existing ocean observing platforms and enhancing support to expand observing along coasts of developing countries, in deep ocean basins, and near the poles; and (4) targeting capacity building efforts. Following these suggestions could help create a coordinated marine biodiversity observing system enabling ecological forecasting and better planning for a sustainable use of ocean resources.

Protecting groundwater levels and ecosystems with simple management approaches - Saskia L. Noorduijn; Peter G. Cook; Craig T. Simmons; Stuart B. Richardson (Hydrogeology Journal, 2019)

Evidence for multiple sensory circuits in the brain arising from the respiratory system: an anterograde viral tract tracing study in rodents - Alice E. McGovern; Nicholas Davis-Poynter; Seung-Kwon Yang; David G. Simmons; Michael J. Farrell; Stuart B. Mazzone (Brain Structure and Function, 2015)

Cloning, sequencing and analysis of the pucC genes from Rubrivivax gelatinosus strain 151 and Rhodopseudomonas acidophila strain 10050 - Adrian E. Simmons; Stuart J. Barrett; C. Neil Hunter; Richard J.R. Cogdell (Photosynthesis Research, 2000)